Properties of Kelempayan particleboard with different resin content (10%, 11% and 12%) - Ripaai, Ahmad Husni; Kamaruddin, Mohamad Amirul; Abdul Karim, Muhammad Syarafi (2012)
The properties of particleboard from kelempayan (Anthocepalus chinensis) species with phenol formaldehyde (PF) resin were study. The effect of different particle size (1.0 mm, and 2.0 mm) and resin contents (10%, 11%, and 12%) on particleboard were determined. Target density of particleboard is 550 kg/m3. The particleboard are tested for physical and mechanical properties using European standard. Mechanical properties similar MOE, MOR, IB and physical properties (thickness swelling and water absorption) were carry out. In general, Kelempayan has significant and non significant on the mechanical properties and physical properties of boards. By using the British standard (BS EN), the board were met the requirement only for mechanical properties, while for physical properties, it do not met the standard.